PEMBELAAN MELALUI PRINSIP-PRINSIP BUSINESS JUDGEMENT RULE BAGI DIREKSI BUMN PERSERO BILA TERJADI KERUGIAN - Kusmono, nFN (Polytechnic of State Finance STAN, 2016)
Limited company as a legal entity (rechtspersoon / legal person) is a Limited Liability Companywhose setting is subject to the realm of private law (Law No. 40 Year 2007 on Limited LiabilityCompanies, but its capital from the separated state wealth is subject to the legal sphere of public law -Law Number 17 Year 2003 on State Finance). Main objective of the State-owned Enterprise as LimitedCompany is doing business with the profit as final target. Business carries the risk of loss, meaning itdoes not always generate benefit. Problems arise when the business decisions taken by the board ofdirectors turn out to bring loss. The problems can be in the forms of the laws to regulate the State-ownedEnterprise, the concept of the separation of state assets, and, the accountability setting of the Board ofDirectors.One of the central government's objectives is to increase the common wealth. In order to fulfill thatobjective, the government needs to create economic growth through government capital at State-ownedEnterprise. Government equity participation to State-owned Enterprise can be performed by usinggovernment budget which is separated from national wealth on the basis of provision mechanism appliedat corporate regulations. The separated national wealth will be converted as State-owned Enterprisecapital when the fund has been deposited. In this case, the government is the share holder in which theshares are the national wealth.The defence of State-owned Enterprise Board of Directors when the company losses is applyinggood faith, duty of care, and duty of loyalty which is regulated through Law of Limited Company 95 No. 5.